CORRELATION OF RADON AND SEISMIC ACTIVITY IN THE BAIKAL RIFT ZONE ACCORDING TO EMANATION MONITORING DATA - K. Zh. Seminsky; А. А. Bobrov (Геодинамика и тектонофизика, 2024)
Long series of the emanation monitoring organized at Tyrgan (2018–2023), Buguldeika (2020–2023) and Maksimikha (2022–2023) stations in the central part of the Baikal Region (the Eastern Siberia) are studied to reveal the relationship of the subsurface radon volumetric activity (RVA) with the seismicity of the Baikal rift zone (BRZ). The comparison of the weekly averaged RVA values at different stations and the degree of dependence of this parameter on the logarithm of the total earthquakes energy (LgΣE) showed that during the periods of seismic activity the impact of tectonic forces makes significant corrections in the character of emanations, which in general is determined by non-tectonic factors. It has been established that seismic activity represented by the enough strong for the Baikal Region earthquakes with K≥13.3 correspond to synchronicity intervals of RVA at different monitoring stations, as well as coincidence of maximum values of the logarithm of the total earthquakes energy with local maximums of the correlation coefficient between RVA and LgΣE parameters. The area, including the earthquake epicenters that generated such an emanation response at monitoring stations, is in the form of an ellipse extended in the northeastern direction – along the main fault structures of the BRZ. The obtained results, besides confirming the previously proposed model of radon field formation in the Baikal Region under the influence of external and internal forces, provide the for the identification of further stable precursors of strong earthquakes based on a comprehensive analysis of data from a branched emanation monitoring network.